O uso do Antigo Testamento em 1Pedro e suas implicações teológicas - Rueda Neto, Eduardo (2024)
The interconnectedness among the texts of the Bible is one of its remarkable characteristics. Particularly, the interdependence between the Old and New Testaments and the way the latter employs the former have captured the attention of scholars. Understanding the nature of this relationship and exactly how it occurs has been considered a significant challenge in the field of biblical studies, and research indicates that there is still much to investigate and debate on the subject. Turning to the books that make up the New Testament, it is possible to see that one of those that most often quote, allude to, or echo the Old Testament is the First Epistle of Peter. Despite its small extension, this epistle contains a very high concentration of connections with Jewish Scriptures, making it a perfect sample of the phenomenon of the use of the Old Testament in the New. Based on this observation, the present research aims to analyze the main Old Testament influences in the composition of 1Peter, in the form of quotations, allusions, and echoes, as well as to examine the theological implications of the relationship between the Petrine letter and the Jewish scriptural body. The first hapter of this study is dedicated to presenting an overview of the debate regarding the use of the Old Testament in the New and, more specifically, the use of the Old Testament in 1Peter. The second and third chapters are devoted to the analysis of inner-biblical links themselves, while the fourth and last chapter seeks to explore the theological consequences of how 1Peter uses the Old Testament. Throughout the course of this research, it was found that the apostolic letter is inseparably linked to the Scriptures of Israel, and it is impossible to fully comprehend it without considering its Old Testament background